Catalogue of type specimens of Insecta (Arthropoda: Hexapoda) deposited in the entomological collection of the Museum of Zoology of Universidade Estadual de Feira de Santana, Brazil - Silva Ferreira, André da; Araújo, Maíra Xavier; Vilarinho, Naiara Thaís; Silva Neto, Alberto Moreira da; Bravo, Freddy (Zootaxa, 2020)
This contribution is an update catalogue of the type specimens of Insecta deposited in the entomological collection Prof. Johann Becker of the Museum of Zoology of Universidade Estadual de Feira de Santana, Bahia, Brazil. A list of 206 holtypes and 1, 430 paratypes of 23 families, 73 genera, and 244 species allocated in 12 orders. Lectotype and paralectotypes of Bitoma palmarum Bondar, 1940 were designated. Diptera present the highest number of types on the collection, with 161 holotypes and 1, 324 paratypes. Copyright © 2020 Magnolia Press.
Keywords: Bahia; Diptera; Information Center; Nonhuman; Zoology